ANALISIS LAPORAN REALISASI ANGGARAN BELANJA UNTUK MENILAI EFISIENSI KINERJA KEUANGAN PADA KECAMATAN DRAMAGA KABUPATEN BOGOR - Dwi Putri Ramahadiyanti; Fujianti, Lailah; Damayanti, Ameilia (FEB-UP Press, 2024)
Budget realization report is very important for an agency or institution, Budget report has a function to find out how the financial condition of a company or institution. The purpose of this study is to analyze how efficient the financial performance of Dramaga District, Bogor Regency through the 2018-2022 Budget Realization Report. The Budget Implementation Report provides an overview of the economic resources managed by local governments and their allocation and use, showing a budget and performance in the reporting period. The method used in this study is quantitative descriptive using the calculation of efficiency ratios. The results showed that the level of shopping efficiency at the Dramaga District Office obtained an average of 93.75% which was included in the inefficient category, this occurs due to the waste of budget because performance-oriented budgeting is not based on needs and considerations alone but also based on predetermined goals where the implementation is focused on efficiency.